Beyond the Scales: Histopathologic Insights into Pityriasis Lichenoides Chronica - Nur Laili, Utiya; Murasmita, Alamanda (Health and Medical Journal, 2025)
Introduction: Pityriasis lichenoides is an inflammatory skin condition characterized by papular, squamous or necrotic lesions. Currently, studies that accurately correlate clinical subtypes with histologic features are rare. The aim of this study is to describe the clinical and histopathologic features of chronic pityriasis lichenoides especially in adults. Case: A 30-year-old male with complaints of reddish papules and nodules on the body and both hands since 10 years ago. The patient initially complained of reddish papules and nodules on the chest then increasingly spread to the whole body, back and both hands. The papules and nodules were slightly painful and did not itch. On histopathological examination, the epidermal layer showed hyperkeratosis, acanthosis, spongiosis and basal cell vacuolization, while the dermis layer showed perivascular infiltrate dominated by lymphocytes with eosinophil cells obtained 1 cell and a little melanin dropping. Discussion: The histopathologic impression supports the diagnosis of chronic pityriasis lichenoides. The histopathologic picture of the patient showed vacuolar interface dermatitis with parakeratosis, exocytosis, erythrocyte extravasation, necrotic keratinocytes, spongiosis and perivascular lymphocytic infiltration. This case report shows the characteristic histopathologic features of lichenoid (interface) dermatitis and lymphocytic vasculitis which are typical histopathologic markers in patients with chronic pityriasis lichenoides. Conclussion: Pityriasis lichenoides is essentially a lymphocytic vasculitis with associated inflammatory cell infiltration showing exocytosis into the epidermis with blurring of the dermoepidermal interface